Injectable and tissue-conformable conductive hydrogel for MRI-compatible brain-interfacing electrodes - Song Dong Kim; Kyuha Park; 이성준; 금정은; Yewon Kim; Soojung An; Kim, Hyungmin; Mikyung Shin; Donghee Son (OAE Publishing Inc., 2023)
The development of flexible and stretchable materials has led to advances in implantable bio-integrated electronic devices that can sense physiological signals or deliver electrical stimulation to various organs in the human body. Such devices are particularly useful for neural interfacing systems that monitor neurodegenerative diseases such as Parkinson’s disease or epilepsy in real time. However, coupling current brain-interfacing devices with magnetic resonance imaging (MRI) remains a practical challenge due to resonance frequency variations from inorganic metal-based devices. Thus, organic conductive materials, such as poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS), have recently been considered as promising candidates. Nonetheless, their conformability on curvilinear tissues remains questionable. In this study, we developed an injectable conductive hydrogel (ICH) composed of tyramine-conjugated hyaluronic acid (HATYR) and PEDOT:PSS for MRI-compatible brain-interfacing electrodes. Our ICH produced low impedance around 5 kΩ even under 10 Hz, demonstrating high confidence volumetric capacitance. Due to HATYR’s biocompatibility, histological and cytotoxicity assays showed almost no inflammation and toxicity, respectively; in addition, ICH was able to degrade into 40% of its original volume within four weeks in vivo. An electrocorticogram (ECoG) array was also patternable by syringe injections of ICH on a stretchable and flexible elastomeric substrate layer that conformed to curvy brain tissues and successfully recorded ECoG signals under light stimulation. Furthermore, MRI imaging of implanted devices did not show any artifacts, indicating the potential of the MRI-compatible hydrogel electrodes for advanced ECoG arrays. This study provides a promising solution for MRI-compatible neural electrodes, enabling the advancement of chronic neural interfacing systems for monitoring neurodegenerative diseases.